Pengaruh Adopsi Teknologi Finansial (Fintech) terhadap Pertumbuhan UMKM - Oktaviani, Wiltri; Y, Yulhendri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Micro, Small, and Medium Enterprises (MSMEs) hold a strategic role in Indonesia’s reeconomy, especially as a major contributor of Gross Domestic Product (GDP) and labor absorption. However, SMEs still face various constraints, notably limited access to capital and markets. The presence of financial technology (financial technology/fintech) becomes an alternative solution to expand access to financing while facilitating financial transactions. This study aims to know the influence of fintech adoption on SME growth. The method used was an explanatory quantitative research with survey technique on a number of fintech user SME respondents in Padang City. Data were analyzed using multiple linear regression with tests of validity, reliability, as well as classical assumptions testing as supporting measures. The study results show that fintech adoption positively and significantly affects the growth of SMEs. The dimensions of ease of use, usefulness, accessibility, and security proved to make a real contribution towards the increase in omzet, the number of customers, as well as the expansion of SMEs’ market access. The conclusion of this study is that the utilization of fintech is capable of driving the growth of SMEs and can be an important instrument in strengthening the competitiveness of small businesses in the digital era.